Application of Ojip Chlorophyll Fluorescence Transient Analysis to Study The Postharvest Changes in Photosinthetic Apparatus in Cut Foliage Species - W M U D Wijethunga; L S H Jayasooriya; S M J C Subasinghe; H M P C Kumarihami; C K Beneragama (Universitas Djuanda, 2021)
Chlorophyll fluorescence (ChlF) is a non-invasive technique that can be potentially used in postharvest research to gain useful information on early responses to postharvest stresses. This study was conducted to validate the application of ChlF transient analysis in determining the postharvest changes in photosynthetic apparatus in three ornamental foliage species, i.e., Cordyline fruticosa ‘Willy’s Gold’ and ‘Rubra’, Dracaena sanderiana ‘White’, and Nephrolepis exaltata. Salicylic acid (100 and 300 mg·L−1), glucose (10 g·L−1), and their combinations were used as holding solutions with control treatment (distilled water) at room temperature (25±2°C). Vase life was evaluated using OJIP analysis. OJIP parameters, i.e., specific energy fluxes per reaction center (ABS/RC, TR/RC, ET/RC, and DI/RC), flux ratios (maximum quantum yield of primary photochemistry-φPo), electron transport efficiency (ψo), and quantum yield of electron transport (φEo), and performance index (PI) were recorded every other day, using a fluorometer (FluorPen 100). Leaf chlorophyll contents of all species and anthocyanin contents of two cordyline cultivars were determined. Data were subjected to ANOVA in a completely randomized design. Mean separation was done by DMRT (p ≤ 0.05). Clear variations in ChlF were observed in every foliage species with the time. OJIP analysis showed species-depended variations. The higher ABS/RC and DI/RC were recorded for D. sanderiana and N. exaltata compared to the PI of those species. At the end of the experiment, the chlorophyll contents were decreased, while anthocyanin contents were increased. Consequently, chlorophyll fluorescence changes in photosynthetic apparatus can be used for the prediction of the postharvest stresses and longevity of cut foliage.